Observation of multiply ionized plasmas with dominant bound electron contribution to the index of refraction - Shlyaptsev, Vyacheslav N., author; Hunter, James R., author; Keenan, Roisin, author; Smith, Raymond F., author; Dunn, James, author; Scofield, J. H., author; Nilsen, Joseph, author; Moon, Stephen J., author; Marconi, Mario Carlos, author; Rocca, Jorge J., author; Filevich, Jorge, author; Elsevier Ltd., publisher (Colorado State University. Libraries, 2006)
We report anomalous fringe shifts observed in soft X-ray laser interferograms of laser-created Al plasmas. This clear experimental evidence shows that the contribution of bound electrons can dominate the index of refraction of laser-created plasmas at soft X-ray wavelengths, resulting in values greater than 1. The comparison of measured and simulated interferograms shows that this results from the dominant contribution of low-charge ions to the index of refraction. This usually neglected bound electron contribution can affect the propagation of soft X-ray radiation in plasmas and the interferometric diagnostics of plasmas for many elements.
Keywords: interferometry; soft x-ray laser; index of refraction; plasmas; anomalous dispersion